A novel missense mutation, I890T, in the pore region of cardiac sodium channel causes Brugada syndrome. - Anna Tarradas (PLoS ONE, 2013)
Brugada syndrome (BrS) is a life-threatening, inherited arrhythmogenic syndrome associated with autosomal dominant mutations in SCN5A, the gene encoding the cardiac Na(+) channel alpha subunit (Na(v)1.5). The aim of this work was to characterize the functional alterations caused by a novel SCN5A mutation, I890T, and thus establish whether this mutation is associated with BrS. The mutation was identified by direct sequencing of SCN5A from the proband's DNA. Wild-type (WT) or I890T Na(v)1.5 channels were heterologously expressed in human embryonic kidney cells. Sodium currents were studied using standard whole cell patch-clamp protocols and immunodetection experiments were performed using an antibody against human Na(v)1.5 channel. A marked decrease in current density was observed in cells expressing the I890T channel (from -52.0 ± 6.5 pA/pF, n = 15 to -35.9 ± 3.4 pA/pF, n = 22, at -20 mV, WT and I890T, respectively). Moreover, a positive shift of the activation curve was identified (V(1/2) = -32.0 ± 0.3 mV, n = 18, and -27.3 ± 0.3 mV, n = 22, WT and I890T, respectively). No changes between WT and I890T currents were observed in steady-state inactivation, time course of inactivation, slow inactivation or recovery from inactivation parameters. Cell surface protein biotinylation analyses confirmed that Na(v)1.5 channel membrane expression levels were similar in WT and I890T cells. In summary, our data reveal that the I890T mutation, located within the pore of Na(v)1.5, causes an evident loss-of-function of the channel. Thus, the BrS phenotype observed in the proband is most likely due to this mutation.